2019
DOI: 10.1177/1120700019859842
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal outcomes after internal fixation for displaced intracapsular femoral neck fractures in 50- to 60-year-old patients

Abstract: Purpose: The aim of this study was to evaluate outcomes of internal fixation for displaced femoral neck fracture (FNF) between 50 and 60 years old. The patient and surgical factors for the failure were identified. Methods: We retrospectively reviewed the records of 102 displaced FNF patients between 50 and 60 years old (mean age 54.9 years) who had undergone internal fixation between 2005 and 2016. The minimum follow-up was 12 months. Primary end points included loss of reduction, non-union, and osteonecrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The elastic modulus of the sclerotic region is three times higher than that of the normal cancellous bone, which is in line with our hypothesis. Moreover, this value is within the range of cancellous bone elastic moduli determined in other studies [17,18] .…”
Section: Measurements Of the Elastic Modulus Of Cancellous Bonesupporting
confidence: 87%
“…The elastic modulus of the sclerotic region is three times higher than that of the normal cancellous bone, which is in line with our hypothesis. Moreover, this value is within the range of cancellous bone elastic moduli determined in other studies [17,18] .…”
Section: Measurements Of the Elastic Modulus Of Cancellous Bonesupporting
confidence: 87%
“…7 Conservative treatment is rarely applied because of poor outcomes. 8 Thus, most femoral neck fractures are treated surgically. Elderly patients with femoral neck fractures often develop ALI, and hypoxaemia is the most common symptom in patients with ALI.…”
Section: Discussionmentioning
confidence: 99%
“…7 Conservative treatment is rarely applied because of poor outcomes. 8 Thus, most femoral neck fractures are treated surgically.…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis study also pointed out that DHS and CS showed no difference in the rates of reoperation, nonunion and mortality, and CS was superior to DHS on femoral head necrosis [34]. Moreover, DHS has the shortcomings of longer operation time, larger operative trauma, more bleeding, less bone preservation after implantation, and more serious bone damage [6]. In contrast, CS has the advantages of less invasion of soft tissues, less bone damage, simpler procedure and so on, which can well avoid the deficiencies of DHS.…”
Section: Discussionmentioning
confidence: 99%
“…However, vertical Pauwels type III FNFs are unstable due to shearing forces [3] and after internal fixation the fracture fragments tend to displace, resulting in a high incidence of complications. According to the literature, the incidence of non-union after internal fixation of Pauwels type III FNF ranges from 16% to over 30%, and the incidence of femoral head necrosis from 11% to over 45%, seriously obstructing the prognosis of patients [4][5][6].…”
Section: Introductionmentioning
confidence: 99%